Análise química e potencial antimicrobiano de óleos essenciais sobre Escherichia coli enterotoxigênica na conservação de carne moída - Souza, Alline Aparecida (2015)
Escherichia coli is considered the main representative bacteria of the family Enterobacteriaceae, belonging to the group of the thermotolerant coliform. Your presence in food shows directly and indirectly contamination of fecal origin. E.coli enterotoxigenic (ETEC), pathogenic strain of the species E.coli, is an important cause diarrhea episode, being the main etiological agent of the disease called traveler’s diarrhea (TD), often found in food, obtained in poor sanitary conditions. Among the various foods associated to intoxications outbreaks, stands out the ground beef, to be commercialized in natura and very manipulated. Being an animal product, there is a high contamination rate by E.coli, and may contain ETEC. Therefore, safe alternatives to commercialize this product shall be proposed. In this context, is highlight the use of essential oils, which are natural compounds of plant origin, show complex chemical composition which makes them capable of performing various pharmacological activities, as the antiseptic action, that has been explored in both medical and pharmacology area as in the food industry, as food preservatives. In view of this, aimed to analyze in vitro the antimicrobial activity of sixteen essential oils over ETEC, selecting the most effective for the synergistic study of your combinations in vitro and in ground beef. The minimum bactericidal concentrations in the essential oils and their combinations was determined by the microdilution method using tryptone soy broth, and 96-well polystyrene microplates with subsequent plating of the cultures in tryptone soy agar. The chemical analyzes of pure oils and their combination were done on GC-MS and GC-FID. For tests in situ, were selected the combinations with the smaller proportions of oregano oil, cinnamon and thyme and oregano, clove and thyme. Both treatments were applied in ground beef portion inoculated with ETEC, which was stored for five days at 7°C. In the analyzes by CG-EM of the treatments, was observed, in both, the majority presence of the compound carvacrol and others as monoterpenes: thymol, p-cymene and γ-terpinene. The colorimetric analysis indicated significant variation in mean values of L *, a *, b *, C * h * in the color of the meat treated with the combination of essential oils. This indicates that the addition of the treatments in ground beef allowed keep the meat looking good during the five days of storage. The essential oils combination showed synergistic effects sufficient to inhibit ETEC in vitro study and this result was repeated, although in reduced form, when these combinations were added to ground beef.